The association between using screen in the dark and depressive symptoms: a longitudinal study among Chinese adolescents - Qu, Shuangxiao; Zhang, Fengyun; Wang, Xuelai; Huang, Shenglei; Zheng, Keyang; Chu, Liting; Huang, Yuting; Yang, Yanting; Yang, Dongling; Luo, Chunyan (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the association between using screen in the dark—a predominant source of LAN—and depressive symptoms in Chinese adolescents.MethodsThis study utilized a sample of 3659 adolescents (51.87% boy, mean age 14.41 ± 1.55 years) from the 2020-2022 Surveillance of Students’ Common Diseases and Health Influencing Factors in Shanghai, China. Baseline screen usage was collected by self-reported questionnaire. Depressive symptoms at baseline, 1- and 2-year follow-up were assessed using the Center for Epidemiology Scale. Generalized estimating equations were used to evaluate the association of using screen in the dark with depressive symptoms.ResultsThe prevalence of depressive symptoms and severe depressive symptoms in this study was 23.59% and 5.25% respectively at baseline. 15.76% adolescents who had depressive symptoms in 2020 aggravated to severe depressive symptoms in 2021 or 2022. 12.38% of the participants reported using screen in the dark. Using screen in the dark was associated with higher likelihood of depressive symptoms (OR = 1.89, 95%CI: 1.67, 2.15) and severe depressive symptoms (OR = 1.89, 95%CI: 1.54, 2.31). The adverse effect of using screen in the dark and screen time > 2 hours/day on depressive symptoms was slightly higher than only screen time > 2 hours/day (OR = 1.24, 95%CI: 1.12, 1.37) or only using screen in the dark (OR = 2.15, 95%CI: 1.73, 2.67). Additionally, those who using screen in the dark combination with screen time > 2 hours/day or insufficient sleep have the highest likelihood of depressive symptoms.ConclusionsScreen use in dark environments independently related to depressive symptoms in adolescents, with compounded associations from excessive screen time and sleep deprivation. These findings underscore the need for public health interventions targeting nighttime digital behaviors.